SOCIAL ACCOUNTING IN SUBSISTENCE AND FAMILY-PRODUCTION TYPE ECONOMIES. - Farman, Wilson L. (The Accounting Review, 1953)
The scheme of social accounts presented and discussed in this paper has made provision for subsistence and family production but has done so within the framework of a separate and segregated sub-sector. Likewise the same scheme of proposed accounts provides for the segregation and separate reporting of barter transactions. As a consequence of the above, provision is made for separate and segregated reporting of all items which have to be based on estimate and imputation and which consequently are subject to a considerable degree of possible error. This facilitates interpretation and evaluation. The remaining segments of an industrially backward economy should be subject to the same scheme of social accounting as that for the Western nations.